Magic Lantern Guides: Konica Minolta Maxxum 5D/Dynax 5D - Peter K. Burian
Konica Minolta's new digital SLR camera-called the Maxxum 7D in North America and the Dynax 7D elsewhere-offers many unique digital SLR features. "Magic Lantern helps users thoroughly understand all its advantages, and goes beyond the user's manual with complete instructions for operating such innovative elements as the exclusive Konica Minolta Anti-Shake System, exposure compensation settings, white balance controls, creative focus control, auto exposure, and honey-comb metering system.